Breaking New Ground: A Comprehensive Review of Advanced Intravaginal Rings in the Management of Hormonal Imbalances in Polycystic Ovarian Syndrome. - Sharma, Tamanna (Journal of Advanced Research in Information Technology, Systems and Management; Vol 8 No 1 (2024): Journal of Advanced Research in Information Technology, Systems and Management, 2024)
This review aims to shed light on the potential of advanced IVRs as a transformative therapeutic tool, paving the way for future research and clinical applications in the tailored management of hormonal imbalances in Polycystic Ovarian Syndrome. Polycystic Ovarian Syndrome (PCOS) is a prevalent endocrine disorder affecting reproductive-aged women, characterized by hormonal imbalances and ovarian dysfunction. This comprehensive review explores the innovative approach of utilizing advanced intravaginal rings (IVRs) as a novel therapeutic strategy for managing hormonal imbalances in PCOS.The paper highlights the Importance of hormones such as estrogen, progesterone, and androgens, which contribute to the syndrome's multifaceted symptomatology. Traditional treatment modalities often fall short in addressing the complex hormonal dysregulation observed in PCOS, prompting the exploration of alternative delivery methods. Intravaginal rings, known for their sustained and controlled release of medications, offer a promising avenue for targeted hormone delivery. The review provides an in-depth analysis of recent advancements in IVR technology, discussing the design, pharmacokinetics, and safety profiles of various prototypes specifically tailored for PCOS management. Furthermore, the paper evaluates the efficacy of IVRs in regulating menstrual cycles, mitigating hyperandrogenism, and improving metabolic parameters in PCOS patients. Insights from preclinical and clinical studies are synthesized, offering a comprehensive overview of the evolving landscape of IVRs in the context of PCOS treatment .